Sharia and Shah Bano: Multiculturalism and Women's Rights - Philips, Amali (Anthropologica, 2022)
This article is a comparative examination of the 2005 sharia controversy surrounding the establishment of faith-based arbitration in Ontario, Canada, and a similar controversy in India after the 1985 Supreme Court Ruling favouring the claim of Shah Bano, a Muslim woman who challenged her husband in court for extended maintenance in contravention of Muslim Personal Law. I use the two controversies to interrogate the contentious issue of group rights and women's rights with particular reference to religious-based personal laws. The two cases demonstrate the patriarchal aspects of personal laws in the private and public realms and their politicization in the public realm. They also underscore the limits of multiculturalism in its potential to deal with the impacts of multicultural accommodation of group rights on the equality rights of women within these groups. My paper emphasizes the need to move beyond multiculturalism and high- lights the strategic importance of mainstreaming feminist citi- zenship and human rights discourses into legal norms and practices relating to family law issues in multicultural societies.